2010
DOI: 10.1177/0956797609360758
|View full text |Cite
|
Sign up to set email alerts
|

The Roots of Bilingualism in Newborns

Abstract: The first steps toward bilingual language acquisition have already begun at birth. When tested on their preference for English versus Tagalog, newborns whose mothers spoke only English during pregnancy showed a robust preference for English. In contrast, newborns whose mothers spoke both English and Tagalog regularly during pregnancy showed equal preference for both languages. A group of newborns whose mothers had spoken both Chinese and English showed an intermediate pattern of preference for Tagalog over Eng… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
192
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 317 publications
(200 citation statements)
references
References 15 publications
(30 reference statements)
4
192
1
3
Order By: Relevance
“…auditory | brain | mother's voice | heartbeat | preterm newborns O ne of the first acoustic stimuli we are exposed to before birth is the voice of the mother and the sounds of her heartbeat. As fetuses, we have substantial capacity for auditory learning and memory already in utero (1)(2)(3)(4)(5), and we are particularly tuned to acoustic cues from our mother (6)(7)(8)(9). Previous research suggests that the innate preference for mother's voice shapes the developmental trajectory of the brain (10,11).…”
mentioning
confidence: 99%
“…auditory | brain | mother's voice | heartbeat | preterm newborns O ne of the first acoustic stimuli we are exposed to before birth is the voice of the mother and the sounds of her heartbeat. As fetuses, we have substantial capacity for auditory learning and memory already in utero (1)(2)(3)(4)(5), and we are particularly tuned to acoustic cues from our mother (6)(7)(8)(9). Previous research suggests that the innate preference for mother's voice shapes the developmental trajectory of the brain (10,11).…”
mentioning
confidence: 99%
“…At birth, infants possess an initial preparedness for language and a developmental readiness that supports learning any of the world's languages (1)(2)(3), yet also already show privileged processing to the native language from prenatal listening experience (4)(5)(6). During the following weeks and months of life, infants become progressively attuned to the properties of their native language, including its rhythmical and segmental (e.g., consonant) information (reviewed in refs.…”
mentioning
confidence: 99%
“…Ramus, Hauser, Miller, Morris, and Mehler (2000) found in their high amplitude test and habituation/dishabituation design that newborns were accustomed to the sentences spoken by two persons in the same language, but not in different languages; in addition, when the language type changed, the newborns' sucking frequency and intensity increased rapidly. Heinlein, Burns, and Werker (2010) proved the result in a high amplitude sucking-preference study. They found that the prenatal bilingual experience even could affect newborns language preference.…”
Section: Introductionmentioning
confidence: 86%